Isolation and Determination of Antioxidant Activity from Methanol Extract of Uncaria cordata (Lour.) Merr. Leaves - Rahmawati, Noveri; Endamora; Rizky Rindiana; Husnunnisa; Irfan, Nawwar; Amini, Rahmi; Putri, Nurdina; Putri Tri Hartini; Khazanah Nurain Nurdin; Restu Anisa Putri; Sari Rahmadhani (The Journal Of Pharmacy, 2026)
Uncaria cordata (Lour. Merr. is one plants genus Uncaria growing in Indonesia, there has been no publication content of secondary metabolites are active as antioxidants. Antioxidant activity by DPPH test (1,1-diphenyl-2 pikrilhidrazil) generate IC50 n-hexane extract did not have IC50 values ​​and can only inhibit 34.234% at a concentration of 1000 µg/mL, ethyl acetate extract of 704.478 µg/mL, methanol extract of 6.778 µg/mL. Methanol extract with the highest IC50 isolation by column chromatography and obtained compound isolates F2. In the test with the Lieberman Burchard color reagent terpenoids positive (red) compounds derived from class terpenoids possibility. The results UV spectrum gives maximum absorption at a wavelength of 293.50 nm and 310.5 nm. Infrared spectrum showed absorption 3410 cm-1 (OH), 2933 cm-1 (CH), 1690 cm-1 (C = O), 1457 cm-1 (CH), and 1036 cm-1 (CC). The antioxidant activity (IC50) F2 compounds have not active category.